Impact of PKSF Cattle Fattening Program on Income, Employment and Livelihood of Participating Farmers in Some Areas of Brahmanbaria and Kishoregonj District - M.R. Hasan; M.I.A. Miah; M.A. Islam; M.N. Uddin (Bangladesh Journal of Extension Education, 2006)
This study examines the impact of micro credit of PKSF on cattle fattening farmers in Brahmanbaria and Kishoreganj district. With the views in mind, 60 project participating farmers were selected purposively from the study area. It is evident that average family size was about 5 persons and about 50% of the project participating farmers have no formal education or can sign only irrespective of areas and farm sizes. The average annual income of landless project participating farmers in Brahmanbaria district increased by 371% while for Kishoregonj it was 258%. The increased income of the small farmers was 160% in Kishoregonj. In Brahmanbaria district, after joining PKSF project the average income from nonagricultural sources increased respectively 58 and 56% for the landless and small farmers and 48 and 46% in Kishoregonj. Total activities of the participating farmers in Brahmanbaria increased by 21.87% for landless and 29.25% for small farmers after participating the PKSF project. The activities of project participating both for landless and small farmers in Kishoregonj district were 24.71 and 26.46. In Brahmanbaria district, value of asset possession of landless farmer increased 120% and 92.74% for small farmers. The asset possession of the landless and small farmer increased by 109.76 and 62.75% respectively after participating the PKSF project. Finally the study concludes that PKSF credit on cattle fattening had positively influenced on income, employment and asset possessions in the project area
Keywords: 330; Income generation; employment creation; asset possession